EFEKTIVITAS GREEN ACCOUNTING SEBAGAI INOVASI DALAM MENINGKATKAN NILAI PERUSAHAAN DI INDONESIA - Rangkuti, May Hana Bilqis; Kumalasari , Fauziah; Agustrisna , Juwita; Munawarah, Munawarah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
In the current Industrialization Era, companies are faced with increasingly competitive competition at local and international levels. This requires the company to continue to compete and maintain the company's performance so that the company can achieve the company's main goals. Maximizing the value of the company is the main goal of the company. In addition to the main goal of maximizing the value of the company, the company must also be oriented towards other aspects known as the triple bottom line, namely profit, planet , and people. And at this time the issue of environmental pollution by the industrial world is a special concern of the Ministry of the Environment. Green accounting has become one of the driving aspects to reduce the threat from environmental pollution. The object of research in all companies engaged in the manufacturing sector that received the PROPER award from the Ministry of the Environment in 2016-2019. This study uses quantitative research methods and types of secondary data. First, financial statements that have been audited and published (companies go public). Second, data from the archives of the Indonesia Stock Exchange (IDX) website, namely the company's annual report for the 2016 – 2019 period. Third, data on the company's environmental performance assessment by the Ministry of Environment for the 2016–2019 period. The data analysis method used is Partial Least Square (PLS) using SmartPLS 3.0 software. The purpose of this research is to prove that the implementation of green accounting can maximize the achievement of company goals.